Modern management of osteoradionecrosis. Issue 4 (August 2018) - Raggio, Blake S.; Winters, Ryan
Abstract : Purpose of review: Despite recent advances in radiotherapy, osteoradionecrosis (ORN) remains a common and difficult complication of radiation therapy in head and neck cancer patients. Available treatment options are complementary to its complex pathophysiology and the currently available theories of ORN development. The efficacy of hyperbaric oxygen therapy has recently been questioned, and therapies targeting the fibroatrophic process have become a focus of ORN treatment. The objective of this review is to evaluate the literature regarding ORN of the mandible, with a focus on available treatment options. Recent findings: The recently proposed fibroatrophic theory has challenged the traditional hypovascular-hypoxic-hypocellular theory as the mechanism of ORN. Medical management targeting this fibroatrophic process offers promising results, but has yet to be confirmed with robust clinical trials. The routine use of hyperbaric oxygen therapy is not substantiated in the literature, but may be justified for select patients. Systemic steroids may also have a role, though data are limited. Summary: The fibroatrophic process has gained acceptance as a main mechanism of ORN. No gold standard treatment or consensus guidelines exist, though a combination of therapeutic strategies should be considered, taking into account the severity of disease and individual patient characteristics.